The role of hydrogen in decarbonizing a coupled energy system. (20th April 2022) - Zhang, Yimin; Davis, Dominic; Brear, Michael J.
Abstract: This paper examines the decarbonization of three coupled energy sectors: electricity, transport and heating/industry. The sector coupling includes the production of hydrogen from each of electricity via electrolysis, the gasification of coal and the reforming of natural gas; the displacement of gasoline/diesel and natural gas by any of these forms of hydrogen; the generation of electricity by gas turbines and reciprocating engines fuelled by either natural gas or any of these forms of hydrogen; and the electrification of the transport fleet. Plausible sensitivities to technological learning, energy efficiency measures, natural gas prices and subsidies for renewables are examined systematically as the coupled system's total greenhouse gas emissions are reduced to zero. The observed transition to zero emissions finds significant uses for hydrogen from both electrolysis and fossil fuels with carbon capture and storage (CCS). Plausible rates of technological learning from today to 2050 dramatically reduce the total costs and the land area required for achieving deep abatement mainly due to the projected fall in the costs of wind, solar PV and electrolysis. The combination of hydrogen fuelled reciprocating engines, electrolysis and hydrogen gas storage is also observed to provide lower cost, long term electricity storage than batteries and pumped hydropower. Nonetheless, the marginal costs of reducing emissions beyond approximately 90% abatement relative to today are always more than 100 /t CO2e and land use can increase dramatically. This suggests that negative emission technologies will likely have a role in achieving net-zero emissions in combination with widespread renewable deployment, technological learning and some continued fossil fuel use with CCS.